Program One Pesantren - One Product in the Perspective of Social Entrepreneurship - Mahfud, Mahfud (Budapest International Research and Critics University, 2021)
One Pesantren-One product is a social entrepreneurship program that has the aim of developing an Islamic boarding school-based economy. Participants of one pesantren one product will be assisted through entrepreneurship training, capital, packaging design and creating an online platform. The aim of the research is to explain the program from a social entrepreneurship perspective. This study used a qualitative approach with a case study method at the Pesantren At-Taqwa Digitalpreneurship. Data collection was carried out by observation, in-depth interviews and literature study. The results showed that the one pesantren-one product program was based on 4 concepts, namely social value, Innovation, civil society and economic activity so that the implementation was in line with the local wisdom of the pesantren itself.